2018
DOI: 10.1007/s00106-018-0507-4
|View full text |Cite
|
Sign up to set email alerts
|

Erkennung und Vermeidung von Schwierigkeiten bei der Tränenwegschirurgie

Abstract: Surgical management of lacrimal duct obstruction beyond the canaliculi proves to be a promising endeavor in most cases. To realize the full potential of endonasal dacryocystorhinostomy, some aspects of diagnosis and differential indication setting should be considered in order to avoid errors and problems during patient selection, execution of the technical procedure, and communication with ophthalmologists. These issues are described according to the clinical management of patients; current literature is cite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
0
2
0
4
Order By: Relevance
“…Various procedures and adjunctive have been studied to improve the success rate of Ex DCR. 13,14 A synthetic corticosteroid, Triamcinolone acetonide (TA), had been used to treat orbital diseases such as thyroid ophthalmopathy, capillary hemangioma of the orbit and idiopathic inflammation of the orbitin the precedent decade. 15,16 Studies have demonstrated a significant independent association with failure in revision external DCR.…”
Section: Discussionmentioning
confidence: 99%
“…Various procedures and adjunctive have been studied to improve the success rate of Ex DCR. 13,14 A synthetic corticosteroid, Triamcinolone acetonide (TA), had been used to treat orbital diseases such as thyroid ophthalmopathy, capillary hemangioma of the orbit and idiopathic inflammation of the orbitin the precedent decade. 15,16 Studies have demonstrated a significant independent association with failure in revision external DCR.…”
Section: Discussionmentioning
confidence: 99%
“…Diese wird durch das Os maxillare (ventral) und das Os lacrimale (dorsal) gebildet. primär mit einem tränenden Auge (Epiphora) manifestieren [14][15][16].…”
Section: Tränenableitungunclassified
“…), sind im Vorfeld zu sanieren. Videoendoskopische Techniken erlauben eine präzise Befunderhebung des mittleren und unteren Nasengangs [13][14][15][16].…”
Section: Benetzungsstörungenunclassified
“…Sie kann anhand von Stenosegrad, -art und -lokalisation, Genese (primär vs. sekundär, ▶ Tab. 2) und Zeitpunkt der Manifestation eingeteilt werden [15][16][17][18][19][20][21].…”
Section: Erkrankungen Der Ableitenden Tränenwegeunclassified